Upfront lower dose lenalidomide is less toxic and does not compromise efficacy for vulnerable patients with relapsed refractory multiple myeloma: final analysis of the phase II RevLite study. (15th February 2017) - Quach, Hang; Fernyhough, Liam; Henderson, Ross; Corbett, Gillian; Baker, Bart; Browett, Peter; Blacklock, Hilary; Forsyth, Cecily; Underhill, Craig; Cannell, Paul; Trotman, Judith; Neylon, Annette; et al.
Summary: The combination of lenalidomide and dexamethasone is an established treatment for patients with multiple myeloma (MM). Increasingly, treatment attenuation is advocated for frail/elderly patients to minimize toxicity even though there have been no prospective studies to demonstrate whether lenalidomide dose attenuation impacts on response and survival outcome. This prospective multicentre phase II study assessed the efficacy and tolerability of lower dose lenalidomide (15 mg) and dexamethasone (20 mg) in 149 eligible patients with relapsed/refractory MM aged over 59 years and/or with renal impairment. The overall response rate was 71% (complete response 15%). Median (range) progression‐free survival (PFS) and overall survival (OS) were 8·9 (6·9–11·5) and 30·5 (20·0–36·2) months, respectively. Upon formal statistical comparison of these endpoints to that of a matched cohort of patients from the pivotal phase III MM009/MM010 studies who received standard‐dose lenalidomide (25 mg) and high‐dose dexamethasone (40 mg) no difference was seen in PFS ( P  = 0·34) and OS ( P  = 0·21). Importantly, grade 3–4 toxicities were reduced with low‐dose lenalidomide, mainly lower neutropenia (29% vs. 41%), infections (23% vs. 31%) and venous thromboembolism (3% vs. 13%). This study supports a strategy of lenalidomide dose reduction at the outset for at‐risk patients, and prospectively confirms that such an approach reduces adverse events while not compromising patient response or survival outcomes.